Breaking the Summer Dormancy of Pinellia ternata by Introducing a Heat Tolerance Receptor-Like Kinase ERECTA Gene - Juneidi, Seifu; Gao, Zengyan; Yin, Huanran; Makunga, Nokwanda P.; Chen, Wei; Hu, Sheng; Li, Xiaohua; Hu, Xuebo (Frontiers in Plant Science, 2020)
Pinellia ternata is a perennial traditional Chinese medicinal plant that undergoes different phenological patterns of dormancy depending on where it is growing. Plants grown in central and southern China typically display two growth cycles every year before and after hot summer days, exhibiting a summer dormancy. However, germplasms from these areas do not go into a dormancy phase in northern China where the summer monthly average temperatures range from 29-31oC. The northern China herbal growers prefer plant stocks from central China due to their longer growing quality and better tuber harvests. Here, we introduced a heat responsive receptor-like kinase ERECTA (ER) gene into P. ternata to explore changes in the growth cycle which were aimed at disrupting the summer dormancy. The 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) gene was also co-transformed with ER to improve the commercial trait. For the thermo-tolerance evaluation, all plants were treated with high temperatures (35oC/40oC) in a growth chamber or grown in natural field temperature in an isolated field before measurement of different agricultural, biochemical and physiological traits. The transgenics showed significantly (P < 0.05) higher heat tolerance, maintaining healthy vegetative growth unlike the empty vector (EV) harboring controls that became chlorotic and necrotic. Better performance in some of the monitored physiological traits was evident for overexpression lines exposed to the heat stress. In open isolated field trials, the transgenic genotypes did not show a summer dormancy but had a survival rate of 84%-95%. The tuber biomasses were also significantly (P < 0.05) higher for the transgenic lines as compared to the EV controls, except for line ER118. Metabolites analysis indicated that the HMGR overexpressing lines (HMGR or HMGR+ER) exhibited significantly higher amounts of bioactive compounds including aromadendrene-4, 10-diol and 4, 8, 13-cyclotetradecatriene-1, 3-diol, 1, 5, 9-trimethyl-12-(1-methylethyl).Our findings show that the summer dormancy of P. ternata which is a naturally evolved trait,can be removed by a single heat responsive gene. The study contributes to generating heat tolerant new Pinellia varieties with enhanced commercially valuable chemicals.